Ordered self-assembly mechanism of a spherical oncoprotein oligomer triggered by zinc removal and stabilized by an intrinsically disordered domain - Smal, Clara (2012)
BACKGROUND: Self-assembly is a common theme in proteins of unrelated sequences or functions. The human papillomavirus E7 oncoprotein is an extended dimer with an intrinsically disordered domain, that can form large spherical oligomers. These are the major species in the cytosol of HPV transformed and cancerous cells. E7 binds to a large number of targets, some of which lead to cell transformation. Thus, the assembly process not only is of biological relevance, but represents a model system to investigate a widely distributed mechanism. METHODOLOGY/PRINCIPAL FINDINGS: Using various techniques, we monitored changes in secondary, tertiary and quaternary structure in a time course manner. By applying a robust kinetic model developed by Zlotnik, we determined the slow formation of a monomeric "Z-nucleus" after zinc removal, followed by an elongation phase consisting of sequential second-order events whereby one monomer is added at a time. This elongation process takes place at a strikingly slow overall average rate of one monomer added every 28 seconds at 20 µM protein concentration, strongly suggesting either a rearrangement of the growing complex after binding of each monomer or the existence of a "conformation editing" mechanism through which the monomer binds and releases until the appropriate conformation is adopted. The oligomerization determinant lies within its small 5 kDa C-terminal globular domain and, remarkably, the E7 N-terminal intrinsically disordered domain stabilizes the oligomer, preventing an insoluble amyloid route. CONCLUSION: We described a controlled ordered mechanism with features in common with soluble amyloid precursors, chaperones, and other spherical oligomers, thus sharing determining factors for symmetry, size and shape. In addition, such a controlled and discrete polymerization reaction provides a valuable tool for nanotechnological applications. Finally, its increased immunogenicity related to its supramolecular structure is the basis for the development of a promising therapeutic vaccine candidate for treating HPV cancerous lesions